2005
DOI: 10.1196/annals.1282.051
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Upregulated H2 Relaxin mRNA Expression during Neuroendocrine Differentiation of LNCaP Prostate Cancer Cells and Production of Biologically Active Mammalian Recombinant 6 Histidine‐Tagged H2 Relaxin

Abstract: Relaxin was recently implicated as a regulator of breast and prostate cancer progression. We characterized upregulated H2 relaxin gene expression during neuroendocrine differentiation of the human prostate cancer model, LNCaP. To examine the impact of relaxin on host cells associated with prostatic adenocarcinomas, we generated recombinant 6 His-tagged relaxin (RLXH) in a mammalian expression system. This immunoreactive and biologically active relaxin preparation was used to screen a variety of cell types for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Similarly, relaxin is produced by the normal prostate (12)(13)(14)(15)(16), and expressed in prostate cancer cell lines LNCaP, DU145, and PC3 (17,18). Relaxin has been implicated in increased tumor growth and angiogenesis of PC3 prostate xenografts (19), whereas we have found that H2 relaxin expression is up-regulated in LNCaP cells undergoing neuroendocrine differentiation (20). Together, these studies strongly implicate relaxin in breast and prostate cancer progression.…”
mentioning
confidence: 52%
“…Similarly, relaxin is produced by the normal prostate (12)(13)(14)(15)(16), and expressed in prostate cancer cell lines LNCaP, DU145, and PC3 (17,18). Relaxin has been implicated in increased tumor growth and angiogenesis of PC3 prostate xenografts (19), whereas we have found that H2 relaxin expression is up-regulated in LNCaP cells undergoing neuroendocrine differentiation (20). Together, these studies strongly implicate relaxin in breast and prostate cancer progression.…”
mentioning
confidence: 52%
“…These data show that relaxin plays a role in p53 R273H -facilitated AI CaP. Interestingly, H2 relaxin mRNA has been shown to be upregulated during neuroendocrine differentiation of LNCaP (Figueiredo et al, 2005). This group reported that induction of neuroendocrine differentiation using epinephrine and interleukin-6 resulted in a 1.5-fold increase in relaxin mRNA expression.…”
Section: Discussionmentioning
confidence: 76%
“…We have studied the tumorigenic effect of RLN, a small peptide hormone produced both in the normal prostate and in prostate cancer (Figueiredo et al 2005, Silvertown et al 2006, Thompson et al 2006, Vinall et al 2006, Feng et al 2007, Liu et al 2008. Previously it has been shown that the RLN expression was increased in aggressive metastatic disease (Figueiredo et al 2005, Thompson et al 2006, Feng et al 2007, and that the stimulation of prostate cancer cells with RLN accelerated their invasiveness, adhesion, survival, and decreased cell apoptosis (Feng et al 2007). Moreover, in the TRAMP mouse model, transgenic overexpression of RLN decreased survival of the males with prostate cancer (Feng et al 2007).…”
Section: Discussionmentioning
confidence: 99%